Design optimization of combined piled raft foundations considering uncertainty. (12th September 2018) - Huber, Maximilian; Dufour, Corentin; Adam, Dietmar; Wieser, Thomas
Abstract: Cities are often seen as centres of economic growth, providing opportunities for study, innovation and employment. An increasing part of the European Union population lives and works in cities and it is widely expected that these patterns will continue as urban areas account for a greater share of activity. This asks for high rise buildings and advanced foundations systems, which are able to transfer high loads from the ground surface into deeper layers. In this contribution we focused on the design optimisation of combined piled raft foundations (CPRF) under uncertainty of load and resistances. We developed a novel optimization algorithm considering the uncertainty of load and resistance parameters. This innovative scheme is applied to an illustrative case study of a combined piled raft foundation in order to show the strength of the proposed approach.